Preparation of Synthetic and Natural Derivatives of Flavonoids Using Suzuki-Miyaura Cross-Coupling Reaction - Hurtová, Martina; Biedermann, David; Osifová, Zuzana; Cvačka, Josef; Valentová, Kateřina; Křen, Vladimír (Molecules (Basel, Switzerland), 2022)
Herein, we report the use of the Suzuki-Miyaura cross-coupling reaction for the preparation of a library of synthetic derivatives of flavonoids for biological activity assays. We have investigated the reactivity of halogenated flavonoids with aryl boronates and with boronyl flavonoids. This reaction was used to prepare new synthetic derivatives of flavonoids substituted at C-8 with aryl, heteroaryl, alkyl, and boronate substituents. The formation of flavonoid boronate enabled a cross-coupling reaction with halogenated flavones yielding biflavonoids connected at C-8. This method was used for the preparation of natural compounds including C-8 prenylated compounds, such as sinoflavonoid NB. Flavonoid boronates were used for the preparation of rare C-8 hydroxyflavonoids (natural flavonoids gossypetin and hypolaetin). A series of previously unknown derivatives of quercetin and luteolin were prepared and fully characterized.
Keywords: kyseliny boronové; molekulární struktura; quercetin; katalýza; Catalysis; Flavonoids; Quercetin; borylation; Luteolin; prenylation; Molecular Structure; flavonoids; Palladium; Boronic Acids; luteolin; palladium; Suzuki–Miyaura cross-coupling reaction; flavonoidy